Pengaruh Work-Family Conflict Terhadap Kinerja Perawat Wanita Dengan Variabel Intervening Komitmen Organisasional Di RSUD Bhakti Dharma Husada Surabaya - Ahmad Hilmy Mubassyir; Nuri Herachwati (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2014)
Women who work and uphold the profession will be more likely to experience conflict, because indirectly he would be having attachment or more concentrate to work and put aside her role as a housewife. A sense that women are more concentrated due to work and put aside domestic affairs, this condition will bring conflicts that arise because they feel neglected work as a housewife in addition also the commitment owned organization, especially among civil servants. Conditions such as this is also the case in the Bhakti Dharma  Husada Hospital Surabaya, increasing consumer complaints in the past few years is an indication of a decrease in the performance of nurses and one of them was allegedly caused by conflicting roles experienced by nurses and resources woman in the hospital. This means that in this case the performance achieved is not in line with expectations because of the role that conflict. This study sample is 46 female nurses in Bhakti Dharma Husada Hospital Surabaya which will be reviewed in terms of work-family conflict and its influence on the performance of the organizational commitment owned. The results of analysis with Partial Least Square show that work-family conflict has no direct influence on the performance of nurses. Meanwhile, with the influence of organizational commitment variables inferred indirectly influence more significant. This suggests that organizational commitment to civil servants clearly will affect the performance without regard to work-family conflict undertaken female nurse.